PENGGUNAAN QR CODE DALAM PEMBELAJARAN POKOK BAHASAN SISTEM PERIODIK UNSUR PADA KELAS X SMA LABSCHOOL UNTAD - Mustakim, Sartika; Walanda, Daud K.; Gonggo, Siang Tandi (Universitas Tadulako, 2013)
Utilization of information technology in particular a QR code in education is still lacking. Therefore the reseacher is examining the QR code in the chemistry learning. Teaching and learning activities in the classroom are still dominated by teachers, meanwhile students seem expect more aids from their peers in performing the task. which due to a number of student are still lack of confidence in completing their tasks. In this study, the researchers use the QR code in the learning of periodic table topics regarding properties of elements. The problem statement was wether the learning outcomes of student who involved in the learning using QR code are better than student who take lessons without involving the use of QR code. The number of student in class X science Labschool Untad for 2013/2014 academic year are 22 student in experimental classroom and 22 student in control classroom which are determined by purposive sampling. Based on the results, it is concluded that the learning outcomes of students who took lessons with the use of QR code is higher than the learning outcome of students who took the lessons without involving the use of QR code for student in class X SMA Labschool Tadulako University.